Mathematics

Question

.−3(4x + 3) + 4(6x + 1) = 43
What is the solution?

1 Answer

  • Answer:

      x = 4

    Step-by-step explanation:

    After you simplify the left side by eliminating parentheses and collecting terms, you have a 2-step linear equation.

      -3(4x +3) +4(6x +1) = 43 . . . . . . given

      -12x -9 +24x +4 = 43 . . . . . eliminate parentheses

      12x-5 = 43 . . . . . . . . . . . collect terms (now a 2-step equation)

      12x = 48 . . . . . . . . . . step 1, add the opposite of the unwanted constant

      x = 4 . . . . . . . . . . . step 2, divide by the coefficient of x

    The solution is x = 4.

    __

    Check

      -3(4·4 +3) +4(6·4 +1) = 43 . . . . substitute for x

      -3(16 +3) +4(24 +1) = 43

      -3(19) +4(25) = 43

      -57 +100 = 43 . . . . . true

NEWS TODAY